Asymmetric Catalysis with Iron–Salen Complexes - Shaw, Subrata; White, James D. (Synthesis, 2016)
Iron(III)–salen complexes based on a chiral cis-2,5-diaminobicyclo[2.2.2]octane scaffold are used as catalysts for a variety of stereoselective reactions. High enantio- and diastereoselectivities can be achieved with these catalysts in sulfa-Michael conjugate addition to acyclic α,β-unsaturated ketones, in regioselective δ-addition of thiols to acyclic α,β,γ,δ-unsaturated ketones, and in Conia-ene carbocyclization of alkynyl-substituted β-dicarbonyl compounds. The use of these chiral iron–salen complexes as catalysts provides a new method for conducting these three important reactions under environmentally sustainable conditions.
Keywords: asymmetric catalysis; ligand; sulfa-Michael additions; carbocyclizations; addition reactions